Analisis Kerentanan Siber Kebocoran Data Polri oleh Bjorka - Mulya, Ilham Indra; L, Lazarus; Saputra, Muhammad Dewanto Adi; Hidayat, Muhammad Rahmadzani (Media Hukum Indonesia (MHI), 2026)
Technological development has transformed many aspects of human life and provided innovations that significantly improve efficiency and convenience. However, the rapid digitalization of society has increased the vulnerability of personal data to cyberattacks and unauthorized access. In Indonesia, public concern over data security escalated following a series of massive data breaches in August 2022, allegedly carried out by an anonymous hacker known as Bjorka. One of the most alarming incidents was the leakage of sensitive data belonging to the Indonesian National Police, revealing critical weaknesses in national cybersecurity systems.This case triggered public distrust and highlighted the urgent need for stronger data protection mechanisms at the state level. Although the government enacted Law Number 27 of 2025 on Personal Data Protection as a legal framework for safeguarding citizens' information, enforcement and implementation remain major challenges. This study aims to analyze the cybersecurity vulnerabilities exposed by the Polri data breach and evaluate Indonesia’s readiness to respond to increasingly complex cyber threats. The research emphasizes the importance of strengthening cybersecurity infrastructure, improving digital literacy, and enhancing regulatory oversight to build a secure, transparent, and trustworthy digital ecosystem.